Perspectives on lecithin from egg yolk: Extraction, physicochemical properties, modification, and applications - Zhao, Feng; Li, Rongji; Liu, Yun; Chen, Haiyan (Frontiers in Nutrition, 2023)
Egg yolk lecithin has physiological activities as an antioxidant, antibacterial, anti-inflammatory, and neurologic, cardiovascular, and cerebrovascular protectant. There are several methods for extracting egg yolk lecithin, including solvent extraction and supercritical extraction. However, changes in extraction methods and functional activity of egg yolk lecithin are a matter of debate. In this review we summarized the molecular structure, extraction method, and functional activity of egg yolk lecithin to provide a good reference for the development of egg yolk lecithin products in the future.